2014
DOI: 10.1111/hex.12327
|View full text |Cite
|
Sign up to set email alerts
|

Is self‐management feasible and acceptable for addressing nutrition and physical activity needs of cancer survivors?

Abstract: Background Self-management is recommended for patients with chronic conditions, but its use with cancer survivors is underexplored. Optimal strategies for achieving lifestyle changes in cancer survivors are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…In addition, effective information delivery and adherence to follow-up with health care professionals are of high priority in cancer care and are key elements of successful implementation of ERAS. In the past, most interventions were delivered face-to-face in either individual or group settings [ 12 , 17 ]. However, a face-to-face approach may not be easy for patients who live far away from the hospital or those who have physical difficulties in travelling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, effective information delivery and adherence to follow-up with health care professionals are of high priority in cancer care and are key elements of successful implementation of ERAS. In the past, most interventions were delivered face-to-face in either individual or group settings [ 12 , 17 ]. However, a face-to-face approach may not be easy for patients who live far away from the hospital or those who have physical difficulties in travelling.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hawkins et al also indicated the importance for patients to possess awareness and a positive belief stance in regard to observing a healthy diet [37]. Nutritional interventions are highly recommended to include as elements of survivorship programs for CRC survivors, because of their potential to improve the general health of such individuals [38]. Nutritional interventions, as part of behaviour-modification programs, have been found to augment the health and quality of life of survivors [30].…”
Section: Resultsmentioning
confidence: 99%
“…Applying the Theory of Planned Behaviour and the Health Action Process Approach, Moug et al indicated the positive role of adopting positive health behaviours, including consuming a healthy diet and avoiding behaviours that put the individual at risk of cancer recurrence [39]; they also recommended CRC survivors to implement dietary interventions that are based on recognizing the role that poor dietary behaviours play in CRC [39]. Additionally, Lawn et al recommended the inclusion of nutritional interventions in self-management strategies for improving CRC survivors’ health and quality of life [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commencing chemotherapy has also been identified as a timely opportunity for receiving information about diet and weight management (James-Martin et al, 2014;Heinze and Williams, 2015;Kelly et al, 2015). Improving nutrition in women during chemotherapy may provide benefits such as enhancing general health and wellbeing (Lawn et al, 2015); enabling women to better cope with chemotherapy side effects (Breast Cancer Care 2014; Boltong and Keast, 2015); and reducing the subsequent risk of cancer recurrence (Tramm et al, 2011).…”
Section: Introductionmentioning
confidence: 99%